Activity Profiles at Different pH and Temperature of Cellulases and Lipases in Freshwater Pearl Mussel: Hyriopsis (Hyriopsis) bialatus, Simpson 1900 - Mayuva Areekijseree; Arunee Engkagul; Uthaiwan Kovitvadhi; Amara Thongpan; Mingkwan Mingmuang; Satit Kovitvadhi (Agriculture and Natural Resources, 2002)
The enzymatic properties of two digestive enzymes, cellulases and lipases, from stomach and intestine of adult freshwater pearl mussel, Hyriopsis (Hyriopsis) bialatus, Simpson 1900, were studied at various pH (1.0-11.0) and temperatures (20-80°C). Activity profiles of both enzymes in male and female mussels at various pH and temperature were similar. Optimum pH of cellulases in stomach and intestine was found to be 6.0 while optimum temperature was 35-55°C in stomach and 30-60°C in intestine. Lipase activity was low in intestine but its optimum pH in both organs was found at pH 8.0 and optimum temperature at 35-55°C. Both cellulase and lipase showed higher activities in the stomach than in intestine. At habitat temperature (28-30°C) of Thai freshwater pearl mussel species, cellulase and lipase specific activities dominated in stomach.